The Gusjigang model for strengthening local wisdom-based character education in digital era - Asror, Moh; Zainiyati, Husniyatus Salamah; Suryani, Suryani (Intelektual Pustaka Media Utama, 2024)
This research aims to analyze Gusjigang (bagus (superior), ngaji (religious science), and dagang (trade)) as a model of strengthening character education based on local wisdom in the digital era. This research methodology uses a systematic literature review with in-depth analysis. The results of this study show that the dimensions of Gusjigang can foster moral goodness, intellectual development, and entrepreneurial spirit. In this case, the younger generation can build a strong ethical foundation, utilize technology wisely, and contribute to the development of themselves and society. By combining Gusjigang values and digital technology, it can create a model of character education that is relevant, strengthens cultural identity, and can adapt to changing times without losing its roots and fundamental values.